Family farming in Brazil: Analysis of the precariousness of work through a systematic mapping - Neto, Antonio de Santana Padilha; Santos, Maria Herbênia Lima Cruz; Pacheco, Clecia Simone Gonçalves Rosa; Santos, Juracy Marques dos; Bomfim, Luciano Sérgio Ventin; Farias, Enos André de (Seven Editora, 2024)
The theme of "precariousness of work" has been arousing the interest of researchers worldwide since the second half of the twentieth century, expanding the debate on this field of study every day, and providing, since then, the generation of a new morphology in the world of work. In family farming, the advent of precariousness has considerably increased the difficulties of rural workers, and consequently, generating increasing social inequalities. This study aimed to analyze published articles on "the precariousness of work in family farming in Brazil" with a time frame of 20 years (2000 to 2020). The method adopted included typical stages of a systematic mapping of literature. As a result of the execution of these steps, a total of 25 articles were analyzed, which allowed us to obtain important elements for a more qualified analysis of this field of study. The findings indicate that the precariousness of work reveals itself as a field of study that potentiates a rupture in the morphology of work, transforming labor relations for rural workers. DOI:https://doi.org/10.56238/sevened2024.007-045